2020
DOI: 10.1016/j.gendis.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of chemoradiotherapy on invasion and metastasis of tumor cells

Abstract: The phenomenon of enhanced invasion and metastasis of residual tumor cells has been observed in an increasing number of patients receiving chemoradiotherapy recently, and tumor metastasis will undoubtedly limit patient prognosis. However, the key mechanism by which chemoradiotherapy affects the invasion and metastasis of tumor cells remains unclear. Studies have shown that chemoradiotherapy may directly act on tumor cells and alter the tumor microenvironment, or induce cell apoptosis and autophagy to promote t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…These results are also in line with literature data, where increased vessel permeabilisation due to 3PO or other means such as radiotherapy or hyperthermia can result in increased metastases. (46) Tumor vessel normalization by means of chemical of pharmacological means has been typically associated with a reduction in tumor malignancy. (47)…”
Section: Evaluation Of 3po Treatment On Metastasesmentioning
confidence: 99%
“…These results are also in line with literature data, where increased vessel permeabilisation due to 3PO or other means such as radiotherapy or hyperthermia can result in increased metastases. (46) Tumor vessel normalization by means of chemical of pharmacological means has been typically associated with a reduction in tumor malignancy. (47)…”
Section: Evaluation Of 3po Treatment On Metastasesmentioning
confidence: 99%
“…It plays an important role in tumor development, maintenance, and progression (15). Studies have shown that autophagy is a double-edged sword, as it promotes CRC invasion and metastasis and CRC cell apoptosis (16,17). Current studies show that tumor autophagy can predict patient prognosis (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that targeting autophagy with natural products could be a potential therapeutic approach for cancer [61,62]. However, autophagy induced by chemotherapy or radiotherapy may impede apoptosis, leading to unfavorable conditions post anti-tumor therapy [63]. Detailed mechanisms of different anticancer drug treatments involving the interplay of autophagy and apoptosis remain poorly understood [64].…”
Section: Discussionmentioning
confidence: 99%